2011
DOI: 10.1128/jb.01343-09
|View full text |Cite
|
Sign up to set email alerts
|

H-NS Binding and Repression of the ctx Promoter in Vibrio cholerae

Abstract: Expression of the ctx and tcp genes, which encode cholera toxin and the toxin coregulated pilus, the Vibrio cholerae O1 virulence determinants having the largest contribution to cholera disease, is repressed by the nucleoid-associated protein H-NS and activated by the AraC-like transcriptional regulator ToxT. To elucidate the molecular mechanism by which H-NS controls transcription of the ctxAB operon, H-NS repression and binding were characterized by using a promoter truncation series, gel mobility shift assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 72 publications
5
48
0
Order By: Relevance
“…For example, nucleoid-associated protein (H-NS) binds DNA at lower temperatures blocking the transcription of multiple genes, whereas higher temperatures cause loosening in the DNA structure allowing transcription to occur. H-NS suppresses virulence-associated genes, such as RTX and CTX, in V. vulnificus (Liu et al, 2009) and V. cholerae (Stonehouse et al, 2011), respectively. The concurrent upregulation of H-NS (ZP_05887985.1) and RTX toxin (ZP_05887531.1) on CPI-1 in the Vc450 proteome at 27 1C could be the result of a conserved Vc450 H-NS unable to regulate a more recently acquired RTX toxin.…”
Section: Temperature-dependent Regulationmentioning
confidence: 99%
“…For example, nucleoid-associated protein (H-NS) binds DNA at lower temperatures blocking the transcription of multiple genes, whereas higher temperatures cause loosening in the DNA structure allowing transcription to occur. H-NS suppresses virulence-associated genes, such as RTX and CTX, in V. vulnificus (Liu et al, 2009) and V. cholerae (Stonehouse et al, 2011), respectively. The concurrent upregulation of H-NS (ZP_05887985.1) and RTX toxin (ZP_05887531.1) on CPI-1 in the Vc450 proteome at 27 1C could be the result of a conserved Vc450 H-NS unable to regulate a more recently acquired RTX toxin.…”
Section: Temperature-dependent Regulationmentioning
confidence: 99%
“…There are numerous evidences indicating that repression by H-NS can be relieved in response to environmental stimuli that activate the expression of other regulators whose binding site overlaps with that of H-NS. For instance, transcriptional silencing of V. cholerae tcpA and ctxA promoters by H-NS is antagonized by the AraC-like transcriptional regulator ToxT and IHF (51,52,59).…”
mentioning
confidence: 99%
“…It has been reported that H-NS function is based on self-oligomerization and binding to DNA motifs to create DNA-protein-DNA bridges that can impede the movement of RNA polymerase (8). H-NS has been shown to repress expression of several virulence genes, including the cholera toxin (ctx) (9,10) and exopolysaccharide biosynthesis (vps) genes in V. cholerae (10,11), the RTX toxin gene (rtxA1) in V. vulnificus (12), and T3SS1 genes in V. parahaemolyticus (13). In many bacterial species, repression by H-NS can be relieved by other regulators, and each bacterial system has developed specific approaches to attenuate the repressive action of H-NS (8).…”
mentioning
confidence: 99%